1996
DOI: 10.1007/bf00837634
|View full text |Cite
|
Sign up to set email alerts
|

Technetium, the missing element

Abstract: The history of the discovery of technetium is reviewed within the framework of the discovery and production of artificial radioactivity in the twentieth century. Important elements of this history are the accidental production of this element in a cyclotron in Berkeley, California, USA, a machine devised by Ernest Orlando Lawrence, and its subsequent discovery in 1937 by Carlo Perrier and Emilio Segrè in scrap metal parts sent by Lawrence to Palermo, Italy by mail. A detailed account is given of the steps take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
0
8
0
3
Order By: Relevance
“…Tc 99m has a half-life of 6.02 hours 21 and decays to the nonradioactive isotope Tc 99 , 22 which is eliminated through the urine and stool. 23 Hypersensitivity reactions to Tc 99m -HDP are extremely rare. The estimated effective radiation dose to a patient undergoing a Tc 99m -HDP bone scan is 2.5 milli-Sieverts (mSv).…”
Section: Discussionmentioning
confidence: 99%
“…Tc 99m has a half-life of 6.02 hours 21 and decays to the nonradioactive isotope Tc 99 , 22 which is eliminated through the urine and stool. 23 Hypersensitivity reactions to Tc 99m -HDP are extremely rare. The estimated effective radiation dose to a patient undergoing a Tc 99m -HDP bone scan is 2.5 milli-Sieverts (mSv).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Tc and Pm, it has been demonstrated that the elements are and were produced by the normal nuclear reactions of stars, but since, their most stable isotopes have a relatively short half-life of 4.21 million years and 17.7 years [27] [28] respectively, by the time scientist are trying to detect them on the earth, there are almost no traces left. After the detection of the neutron star crash it is accepted that all the now called synthetic elements were also produced in that event, but they are not detectable on the earth because of their short half-lives [29].…”
Section: The Synthetic Elements and The Astrophysical Phenomenamentioning
confidence: 99%
“…Whereas [ 99m TcO 4 ] -has been used for thyroid imaging since the 1960s, the preparation of more specific compounds for functional imaging was the incentive which boosted technetium chemistry over the following decades. [25,26] This research comprised all fields; organometallic chemistry and coordination chemistry, thermodynamics and kinetics and even catalysis was an issue. The motivation, however, was mainly the discovery of new imaging agents.…”
Section: Columnsmentioning
confidence: 99%